2013
DOI: 10.1128/aem.00493-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Genotypes and Antibiotic Resistances of Campylobacter jejuni and Campylobacter coli on Chicken Retail Meat and at Slaughter

Abstract: cMultilocus sequence typing (MLST) and antibiotic resistance patterns of Campylobacter jejuni and Campylobacter coli from retail chicken meat showed high overlap with isolates collected at slaughterhouses, indicating little selection along the production chain. They also showed significant common sequence types with human clinical isolates, revealing chicken meat as a likely source for human infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
2
21
1
Order By: Relevance
“…In this study, analysis of the genetic similarities between isolates revealed similar results to those previously reported, i.e. suggesting that C. coli isolates were less diverse, based on the AFLP profiles, that C. jejuni isolates [ 39 ], probably due to C. coli showing more host specificity than C. jejuni [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, analysis of the genetic similarities between isolates revealed similar results to those previously reported, i.e. suggesting that C. coli isolates were less diverse, based on the AFLP profiles, that C. jejuni isolates [ 39 ], probably due to C. coli showing more host specificity than C. jejuni [ 40 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our analyses indicated 31% of cattle strains being resistant to quinolones, and only 1% resistant to macrolides (represented by only one C. coli strain). Similar rates of resistance were found in Switzerland for Campylobacter isolated from other animal species like chicken, pig and dog [29][30][31]37]. Antibiotic resistance is more pronounced in human isolates whereas macrolide resistance is virtually absent [5].…”
Section: Discussionsupporting
confidence: 71%
“…The results of a previous study by Padungtod et al (2006) on the level of resistance in isolates from chicken cecal contents and chicken meat also showed similar resistance between these two sectors. Another study, conducted in Switzerland by Kittl et al (2013), demonstrated considerable overlap in the AMR level of Campylobacter isolates collected from chickens in abattoirs in comparison with isolates obtained from chicken meat at retail. In addition, Idris et al (2006) found that fluoroquinolone resistance in Campylobacter can spread through an integrated commercial poultry production system from parental flocks to their progeny as both groups were colonized by the same strain of resistant C. coli.…”
Section: Discussionmentioning
confidence: 99%